2019
DOI: 10.1177/0363546519879138
|View full text |Cite
|
Sign up to set email alerts
|

Does Injection of Hyaluronic Acid Protect Against Early Cartilage Injury Seen After Marathon Running? A Randomized Controlled Trial Utilizing High-Field Magnetic Resonance Imaging

Abstract: Background: Previous studies have shown that runners demonstrate elevated T2 and T1ρ values on magnetic resonance imaging (MRI) after running a marathon, with the greatest changes in the patellofemoral and medial compartment, which can persist after 3 months of reduced activity. Additionally, marathon running has been shown to increase serum inflammatory markers. Hyaluronic acid (HA) purportedly improves viscoelasticity of synovial fluid, serving as a lubricant while also having chondroprotective and anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The cartilage thickness was used to quantitatively describe the morphological condition of knee cartilage. The cartilage thickness of each subregion was calculated by averaging the minimum distance of each point on the cartilage surface to the corresponding bone–cartilage interface across all segmented slices for each runner based on the GRE magnitude image 29 . The declined morphology would be reported if there was obvious thinning in cartilage.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cartilage thickness was used to quantitatively describe the morphological condition of knee cartilage. The cartilage thickness of each subregion was calculated by averaging the minimum distance of each point on the cartilage surface to the corresponding bone–cartilage interface across all segmented slices for each runner based on the GRE magnitude image 29 . The declined morphology would be reported if there was obvious thinning in cartilage.…”
Section: Methodsmentioning
confidence: 99%
“…The cartilage thickness of each subregion was calculated by averaging the minimum distance of each point on the cartilage surface to the corresponding bonecartilage interface across all segmented slices for each runner based on the GRE magnitude image. 29 The declined morphology would be reported if there was obvious thinning in cartilage. Obvious thinning was defined as more than a 50% reduction of cartilage thickness.…”
Section: Morphological Assessmentmentioning
confidence: 99%
“…However, these methods have achieved limited success. HA offers little protection against early cartilage damage ( Nathani et al, 2019 ). Microfracture is used to treat small articular cartilage lesions that form fibrocartilage and are therefore mechanically weak and prone to degeneration ( Benthien and Behrens, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study found elevated T2-relaxation values within the articular cartilage of the knee after marathon exercise in a high BMI population, presumably as a result of changes in biochemical indicators of articular cartilage ( 28 ). However, it has also been found that such tissues do not undergo morphological changes ( 29 ). The fact that knee cartilage can recover its structural and functional properties after being subjected to running-related loads reflects the fact that articular cartilage can withstand higher loads and repeated stimulation after short periods of rest.…”
Section: Discussionmentioning
confidence: 99%